LMNA R482L mutation causes impairments in C2C12 myoblasts subpopulations, alterations in metabolic reprogramming during differentiation, and oxidative stress - Ivanova, Oksana A.; Predeus, Alexander V.; Sorokina, Margarita Y.; Ignatieva, Elena V.; Bobkov, Danila E.; Sukhareva, Kseniia S.; Kostareva, Anna A.; Dmitrieva, Renata I. (Scientific reports, 2025)
LMNA mutations causing classical familial partial lipodystrophy of Dunnigan type (FPLD2) usually affect residue R482. FPLD is a severe metabolic disorder that often leads to cardiovascular and skeletal muscle complications. How LMNA mutations affect the functional properties of skeletal muscles is still not well understood. In the present project, we investigated the LMNA-R482L mutation-specific alterations in a transgenic mouse C2C12 cell line of myoblasts. Using single-cell RNA sequencing we have studied transcriptional diversity of cultured in vitro C2C12 cells. The LMNA-R482L mutation induces changes in C2C12 cluster composition and increases the expression of genes related to connective tissue development, oxidative stress, stress defense, and autophagy in a population-specific manner. Bulk RNA-seq confirmed these results and revealed the dysregulation of carbohydrate metabolism in differentiated R482L myotubes that was supported by ATP production profile evaluation. The measurement of reactive oxygen species (ROS) levels and glutathione accumulation in myoblasts and myotubes indicates R482L mutation-related dysregulation in mechanisms that control ROS production and scavenging through antioxidant glutathione system. The increased accumulation of autophagy-related structures in R482L myoblasts was also shown. Overall, our experiments showed a connection between the redox status and metabolic alterations with skeletal muscle pathological phenotypes in cells bearing pathogenic LMNA mutation.